L’Éthiopie sportive pré-marathonienne 1924-1960 - Gaudin, Benoit (Aethiopica, 2009)
This paper presents the apparition of modern sport in Ethiopia: in the schools, the military institutions and, as far as football is concerned, in clubs. The foundation of the first local football teams coincides with the raise of the first expressions of an Ethiopian national feeling on the occasion of confrontations against “foreign”, and later Erytrean, teams. After World War II, and through the action of Ydneqatchew Tessema, the first sport institutions of the country are founded. Athletics, which is not yet the vector of the Ethiopian sport nationalism, grows mostly after 1947 with the help of the Swedes. Yet, among the Ethiopian sports of that period, athletics remains in the backstage, restricted to the schools grounds and the military barracks. In accordance with the opinions of the time on the aptitudes of Black people, Ethiopian athletics concentrate then on sprint, and not on long distance races.